ANALISIS KINERJA ORGANISASI SEKERTARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN KUTAI BARAT - Pidesia .; Abdullah Karim; Bambang Irawan (Jurnal Administrative Reform, 2017)
The purpose of this study is to describe and analyze the performance of the organization as well as those factors that inhibit the performance of the organization and supporting the Secretariat of the Regional Representatives Council Kutai Barat. The study concluded that the planning performance on Parliament Secretariat of West Kutai has been through the mechanisms and stages in accordance with the provisions of that starts with formulating a strategic plan is then translated into the annual performance plan, subsequently submitted and approved budget is needed then set a performance evaluation is the ability of the receiver mandate to realize the performance as planned, therefore the performance planning or annual work plan that is the basis for preparing the performance indicators.